Factor Analysis - Factors That Affect Compliance Individual Taxpayer Tax - Ingra Sovita (GLOBAL SCIENTS PUBLISHER, 2024)
This study explains the analysis of factors that affect the tax compliance of Individual Taxpayers at KPP Pratama Padang. In this study, the data used are primary data and secondary data. The sample was taken using the random sampling method using the Slovin formula and a sample of 100 respondents was obtained. The research instrument used was a questionnaire that had previously been tested and had met the validity and reliability requirements, while for data analysis using multiple linear regression analysis. The results of statistical processing assisted by the SPSS 21.0 for widows program show that the influence of independent variables (Tax Knowledge (X1), Tax Sanctions (X2), and Fiscal Service Quality (X3)) on dependent variables (tax compliance) is able to contribute 82.9%, while the remaining 17.1% is explained by other variables that are not included in this study. The results of the study show that partially and simultaneously through the t-test and the f test of the variables Tax Knowledge (X1), Tax Sanctions (X2), and Fiscal Service Quality (X3), have an effect on tax compliance at KPP Pratama Padang